Knowledge, Attitude, Awareness, and Perceptions among Physicians toward Antibiotic Resistance in Hospitals in South Palestine - Jabbarin, Hussein; Nawajah, Inad; Hejaz, Hatem A. (Avicenna Journal of Medicine, 2023)
Background Antibiotic resistance is a global problem, and the World Health Organization has made this problem one of its priorities for solving. Therefore, a survey was carried out to investigate the knowledge, attitude, awareness, and perceptions of antibiotic resistance among physicians and to assess the correlation between the knowledge of antibiotic resistance and their years of experience in some Palestinian hospitals.Methods This was a cross-sectional study that targeted physicians who are working in different healthcare facilities in Hebron and Bethlehem governorates. We used a questionnaire for data collection. The questionnaire consists of 42 questions to measure the knowledge, attitudes, awareness, and perceptions of antibiotic use and resistance.Results The response rate was 91.33% (137 of 150 physicians completed the questionnaire). The participants' ages ranged from 25 to 56 years, and the majority were males (n = 116, 84.7%) working in governmental hospitals (n = 83, 60.6%). Of physicians, 69.3% (n = 95) perceived antibiotic resistance as a very important worldwide problem, while 54.7% (n = 75) perceived a very important problem in the country, 54.0% (n = 74) a very important problem in their hospital, and 59.1% (n = 81) a very important problem in their departments. Methicillin-resistant Staphylococcus aureus was the most known antibiotic-resistant bacteria followed by extended-spectrum beta-lactamases. Only 47 physicians (34.3%) think that antibiotics are not used appropriately in their department. Respondents' physicians showed that the development of antibiotic resistance was due to various factors that include self-medication n= (92, 67.2%), overuse of antibiotics (n = 83, 60.6%), and uncompleted treatment (n= 87, 63.5). Senior specialists/consultants were found to be more knowledgeable about antibiotic resistance.Conclusion In our survey, physicians showed variable knowledge and perceptions of antibiotic resistance. Introducing educational programs is necessary to improve their understanding and perceptions of antibiotic resistance, as well as their attitude toward antibiotic use.
Keywords: antibiotic resistance; physicians; knowledge; attitude; awareness; perceptions; antibiotics